prove

Asked by  | 24th Apr, 2008, 06:58: PM

Expert Answer:

sec A ( 1 - sinA ) ( sec A + tan A)  =1

RHS

=(sec A - sec A sin A) ( sec A + tan A)

=sec 2A - sec 2A sin A + secA tan A- sec A sin A tan A

=1/ cos2A   -  sin A /cos2A  + sin A/ cos2A   -- sin2A  / cos2A

=sec2A  --  tan2A

=1 LHS

tan 2A - Tan2B = sin2A  - sin2B /cos2A cos2B

this qn  LHS  request clarify

Answered by  | 24th Apr, 2008, 10:39: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.